HUBUNGAN STATUS GIZI TERHADAP MOTOR EDUCABILITY MURID SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Syahruddin Syahruddin; Mirfan Irfan Hasanuddin (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
This study aims to obtain answers to problems regarding the relationship between nutritional status and motor educability of students at SD Muhammadiyah Perumnas Makassar City. The research population used in this study were all students of SD Muhammadiyah Perumnas as many as 110 people. The type of research used in this study is the type of correlation, which means that all students in SD Muhammadiyah Perumnas Makassar City. Based on the results of the data analysis of nutritional status variables after being analyzed, it can be said that the nutritional status of the Muhammadiyah Perumnas Elementary School Makassar City as a whole can be said that their nutritional status is included in the "Above Medium" category based on the value of the category threshold table from Glinka quoted from Dr. Dissertation. Sudirman Burhanuddin, namely 1.26 – 1.32 by 23.8% or 10 students from 42 samples studied in this study. From the descriptive analysis of the frequency, it is also known that there are several variations in other categories, namely for the "Very high" category there are 2 people (4.8%), for the "high" category = 5 students (11.9%), the "Low medium" category = 7 students (16.7% ), category "Low" = 7 students (16.7%) and category "very low" = 11 students (26.2%). The results of the analysis of the data above from 42 students of the nutritional status of SD Muhammadiyah Perumnas Makassar City students in the "Above moderate" category can occur because of the alleged influence of the socioeconomic status of parents. The socio-economic factors of parents include indicators of parental education, income, expenditure, and ownership of parents' facilities and infrastructure.